From Gratification to Purchase Intention: Examining the Effects of Social Media Marketing in F&B Through Brand Awareness and Consumer Brand Engagement - Bintang Gustiady; Rina Suthia Hayu (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study aims to analyze the effect of Social Media Marketing on Purchase Intention in the context of the viral food brand Mie Gacoan and to examine the mediating roles of Brand Awareness and Consumer Brand Engagement. This study is motivated by TikTok's growing role as a digital marketing medium capable of shaping brand recognition, consumer engagement, and purchase intention through entertaining, trend-oriented content supported by electronic word of mouth. This research employs an explanatory quantitative approach, with data collected through an online questionnaire administered to 450 respondents aged 18-34 years in Indonesia who had seen Mie Gacoan social media content and had an interest in, or intention to, purchase the product. The data were analyzed using Partial Least Squares-Structural Equation Modeling with SmartPLS. The findings show that Social Media Marketing has a positive and significant effect on Brand Awareness, Consumer Brand Engagement, and Purchase Intention. Brand Awareness and Consumer Brand Engagement also have positive and significant effects on Purchase Intention. The R-square value indicates that the combination of Social Media Marketing, Brand Awareness, and Consumer Brand Engagement explains 61.70% of the variation in Purchase Intention. Moreover, the mediation test results demonstrate that Brand Awareness and Consumer Brand Engagement mediate the effect of Social Media Marketing on Purchase Intention. These findings confirm that social media marketing can increase purchase intention not only directly but also by strengthening brand awareness and consumer engagement.